2021
DOI: 10.1001/jamaophthalmol.2021.0341
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Cumulative Incidence and Severity of Primary Open-Angle Glaucoma Among Participants in the Ocular Hypertension Treatment Study After 20 Years of Follow-up

Abstract: IMPORTANCEOcular hypertension is an important risk factor for the development of primary open-angle glaucoma (POAG). Data from long-term follow-up can be used to inform the management of patients with ocular hypertension. OBJECTIVE To determine the cumulative incidence and severity of POAG after 20 years of follow-up among participants in the Ocular Hypertension Treatment Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Recently a prediction model was applied to the Ocular Hypertension Treatment Study (OHTS 3). 40 The model accounted for baseline age, IOP, central corneal thickness, vertical cup-disc ratio and VF pattern standard deviation; baseline categorisation into low-, medium-, and high-risk tertiles led to 20-year cumulative incidences of POAG representative of the baseline risk groups. Future such tools must be able to automatically incorporate metrics of optic nerve head, nerve fibre layer and macular imaging, rates of VF change, as well as information from electronic patient records.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a prediction model was applied to the Ocular Hypertension Treatment Study (OHTS 3). 40 The model accounted for baseline age, IOP, central corneal thickness, vertical cup-disc ratio and VF pattern standard deviation; baseline categorisation into low-, medium-, and high-risk tertiles led to 20-year cumulative incidences of POAG representative of the baseline risk groups. Future such tools must be able to automatically incorporate metrics of optic nerve head, nerve fibre layer and macular imaging, rates of VF change, as well as information from electronic patient records.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 However, after the development and validation of the risk estimation calculators using the results of the Ocular Hypertension Treatment Study and the European Glaucoma Prevention Study, glaucoma has been the front runner in its clinical application. 16 , 17 Although new biomarkers may modify the original interpretation, 18 currently its use has still a role as a supplementary tool to help decide which patients would benefit the most from treatment. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Population‐based studies have shown a direct correlation between IOP levels and POAG prevalence; however, IOP levels higher than 21 mmHg is a parameter associated with a wide range of glaucoma frequency in different populations (e.g., 71.0% in Barbados vs. 13.0% in the Northeast Italy) 24–26,71,73–75 . Moreover, some patients present glaucoma with no high IOP levels (normal tension glaucoma), and others with ocular hypertension do not display any glaucomatous visual field defect after a long period of time 76 . Ocular perfusion pressure has also been considered another risk factor for POAG; however, it may be a confounder since IOP impacts negatively ocular perfusion pressure calculation 77–79 …”
Section: Risk Factors For Glaucoma Developmentmentioning
confidence: 99%
“…[24][25][26]71,[73][74][75] Moreover, some patients present glaucoma with no high IOP levels (normal tension glaucoma), and others with ocular hypertension do not display any glaucomatous visual field defect after a long period of time. 76 Ocular perfusion pressure has also been considered another risk factor for POAG; however, it may be a confounder since IOP impacts negatively ocular perfusion pressure calculation. [77][78][79]…”
Section: Elevated Iopmentioning
confidence: 99%